Method for producing ceramic-metal bonded body

By heating and supplying metal materials with a laser beam on the surface of the ceramic substrate, the formation of a ceramic-metal joint is achieved, and the problem of difficulty in forming a thin line-shaped metal layer on the ceramic substrate in the prior art is solved, and efficient bonding is achieved for the circuit pattern of the insulating substrate.

CN119654211APending Publication Date: 2025-03-18OSAKA UNIVERSITY +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380053998.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-20
Filing Date
2023-10-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to directly bond the copper-based or silver-based metal layer in a thin line shape on the surface of the ceramic substrate, especially in industrial applications, and the applicability of copper-based metals is insufficient.

Method used

The formation of a ceramic-metal joint is achieved by scanning and irradiating the surface of the ceramic substrate with a laser beam and supplying solid metal material to the surface of the ceramic substrate so that it melts and covers the ceramic surface under the action of the laser beam.

Benefits of technology

A thin line-shaped metal layer with a width of less than 0.5 mm is directly formed on the surface of the ceramic substrate, which is suitable for the formation of an insulating substrate circuit pattern for semiconductor component installation, and can be used to prepare selective bonding between silver-based brazing materials and ceramic plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654211A_ABST
    Figure CN119654211A_ABST
Patent Text Reader

Abstract

The metal layer is directly bonded to the surface of the ceramic substrate in a fine line shape. In a method for manufacturing a ceramic-metal bonded body, irradiation is performed while scanning the surface of a ceramic base material with a laser beam, and a region (hereinafter referred to as an irradiation region) on the surface of the ceramic base material to which the laser beam is irradiated is irradiated at the same time. And) feeding a solid metal material, causing the metal material to be irradiated by the laser beam while being fed, melting the metal material while heating the surface of the ceramic base material located in the irradiation region, and solidifying the molten metal material after covering the surface of the ceramic base material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a ceramic-metal joint body in which a metal material melted by a laser beam is directly joined to the surface of a ceramic substrate. Background Art

[0002] Ceramic-metal joints, i.e., composite materials in which ceramic and metal are integrated via the joints of the two, can be used, for example, in insulating circuit substrates for mounting semiconductor elements. Generally, in the manufacture of insulating circuit substrates, the following method is adopted: after a copper-based or aluminum-based metal sheet member is joined to the surface of a ceramic substrate, unnecessary parts of the metal sheet member are removed by etching to form a circuit pattern. In this case, the process of forming the circuit pattern requires the steps of forming a resist film, etching processing, and removing the resist film, resulting in an increase in manufacturing load and cost.

[0003] As a method for directly forming a metal layer arranged corresponding to a prescribed circuit pattern on the surface of a ceramic plate, a "melt bonding method" is known. The melt bonding method solidifies molten metal on the surface of a ceramic plate set in a mold, and the arrangement of the metal layer bonded to the surface of the ceramic plate can be set according to the gap pattern in the mold. However, it is difficult to form a metal layer in a thin wire shape using the melt bonding method. In addition, although the melt bonding method can be applied to aluminum-based metals, it is difficult to be applied to copper-based metals with high melting points in industry.

[0004] As a method for directly bonding copper-based metals to the surface of ceramics, the technology of spraying is known. For example, Patent Document 1 shows the following example: a plasma spraying method in which copper powder is supplied to a hot gas flow using a plasma burner is used to form a copper layer with a thickness of 75 μm (Example 1) or 30 μm (Example 2) on the surface of a roughened aluminum oxide plate. Patent Document 2 shows the following example: a spraying method such as arc spraying, plasma spraying, and flame spraying is used to spray aluminum, nickel, copper, stainless steel, and other metals on the surface of a ceramic substrate such as aluminum nitride to form a conductive film with a thickness of 50 μm to 1.5 mm (Examples 1, 6, and 7). However, it is difficult to form a metal layer in a thin wire shape using the spraying method.

[0005] As a method of joining a ceramic plate to a metal material surface, there is "brazing". In brazing, a brazing material is applied to the joining interface between the materials to be joined. As representative brazing materials, silver paste and Ag-Cu alloy sheets can be listed. In order to use such a brazing material, it is necessary to apply a brazing material paste to the joining surface of the materials to be joined before brazing, or to prepare a brazing material sheet of a specified shape and arrange it at a specified position between the materials to be joined. If a "brazing-integrated ceramic plate" in which a specified amount of brazing material can be selectively joined to the portion of the ceramic plate that becomes the joining surface can be prepared in advance, it can help reduce the load of the brazing process. It is not easy to form a thin brazing material layer composed of a small amount of silver-based metal at a specified position of the ceramic plate by using a spraying method.

[0006] On the other hand, as a method for coating the surface of a metal substrate with a different metal, "laser metal deposition" is known. This is a technique that uses a laser beam to melt a metal powder as a coating material near the surface of a metal substrate and coats the metal substrate with the molten metal. For example, Patent Document 3 discloses a powder coating (cladding) device that uses multiple laser beams simultaneously.

[0007] Patent document 4 discloses a coating method for forming a copper coating on the surface of stainless steel as a substrate by supplying copper powder as a coating material into a laser beam. Specifically, the following example is shown: using a mixed powder composed of two kinds of pure copper with different particle sizes, the focusing diameter of the cyan laser is set to about 0.5 mm, the scanning speed is 4 mm / s, and the laser output power is changed in the range of 20 to 80 W, and a linear coating is formed on the surface of SUS304 as an object (substrate) (paragraphs 0054 to 0057).

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Publication No. 7-501855

[0011] Patent Document 2: Japanese Patent Application Publication No. 2006-89290

[0012] Patent Document 3: WO2017 / 170890

[0013] Patent Document 4: Japanese Patent Application Publication No. 2022-13563 Summary of the invention

[0014] Problems to be solved by the invention

[0015] According to the laser metal deposition technology, a pure copper coating layer in the shape of a thin line with a line width of, for example, about 0.5 mm can be formed on the surface of a metal substrate, as shown in the example of Patent Document 4. However, compared with the case where the substrate is a metal, it is more difficult to join layers of various metals such as copper and silver to the surface of a ceramic substrate in the shape of thin lines, and the technology has not yet been established.

[0016] An object of the present invention is to provide a ceramic-metal bonded body utilizing a technique capable of directly bonding a metal layer in a thin wire shape to the surface of a ceramic substrate.

[0017] Means for solving problems

[0018] As a result of the research conducted by the inventors, it was found that by using a laser beam to make the surface of the ceramic substrate fully heated, the laser metal deposition method can be used to achieve the joining of ceramic and metal. If the substrate is a metal, as taught in Patent Document 4, by setting the conditions so that the sprayed coating material metal (melt) is preferentially melted and the melting of the metal substrate (object) is suppressed to a minimum, the molten coating material metal (melt) adheres to the surface of the metal substrate (object) and then naturally cools and solidifies, and the surface of the metal substrate (object) can be coated with a coating composed of a metal film without a molten pool (Paragraph 0034 of Patent Document 4). That is, the molten metal is relatively easy to adhere to the surface of the solid heterogeneous metal. However, in the case where the substrate is a ceramic, it is difficult to join the ceramic with the solidified product of the coating material metal under the laser irradiation conditions to the extent that the coating material metal is simply melted directly above the ceramic substrate. In order to obtain a ceramic-metal joint body by a laser metal deposition method, it is important to sufficiently heat the surface of the ceramic as a substrate so that the melt of the coating material metal supplied in sequence is coated on the surface of the ceramic. The present invention is completed based on such a finding. Specifically, the following invention is disclosed in this specification.

[0019] [1] A method for manufacturing a ceramic-metal joint, wherein a laser beam is used to scan the surface of a ceramic substrate while irradiating it, and solid metal material is fed to an area on the surface of the ceramic substrate irradiated with the laser beam (hereinafter referred to as the "irradiation area") so that the metal material being fed is also irradiated by the laser beam, and the surface of the ceramic substrate located in the irradiation area is heated while the metal material is melted, and the molten metal material covers the surface of the ceramic substrate and then solidifies.

[0020] [2] The method for producing a ceramic-metal joint according to [1] above, wherein the solid metal material is a powder.

[0021] [3] A method for manufacturing a ceramic-metal joint according to [1] or [2] above, wherein the solid metal material has any one of Cu, Ag, Ti, Ni, Al, Fe, Au, and Pt as a main component.

[0022] [4] The method for producing a ceramic-metal joint according to [1] or [2] above, wherein the solid metal material contains Cu or Ag as a main component.

[0023] [5] A method for manufacturing a ceramic-metal joint according to any one of [1] to [4] above, wherein one or more laser beams are used and at least one of the laser beams irradiating the metal material being fed has a wavelength of 600 nm or less.

[0024] [6] A method for manufacturing a ceramic-metal joint according to any one of [1] to [4] above, wherein one or more laser beams are used, and at least one of the laser beams irradiating the metal material being fed uses any one of a Yb-doped solid laser, a Nd-doped solid laser, a GaN semiconductor laser, a copper vapor laser, an Ar gas laser, a N2 gas laser, and an excimer laser as a light source.

[0025] [7] The method for producing a ceramic-metal joint according to any one of [1] to [6] above, wherein the solid metal material contains Cu as a main component and the ceramic substrate contains AlN as a main component.

[0026] [8] The method for producing a ceramic-metal joint according to [7], wherein one or more laser beams are used, and the average irradiation energy density E expressed by the following formula (1) is 80 to 160 J / mm 2 The laser beam is irradiated onto the surface of the ceramic substrate.

[0027] E=(P L1 / D L1 +P L2 / D L2 +···+P Ln / D Ln ) / v…(1)

[0028] in,

[0029] E: Average irradiation energy density E (J / mm 2 )

[0030] Symbol Li (i=integer greater than or equal to 1 and less than or equal to n, where n is the total number of laser beams used): identification symbol of each laser beam used

[0031] P Li : Laser output power of laser beam Li (W)

[0032] D Li : The irradiation spot diameter at right angles to the scanning direction of the laser beam Li (mm)

[0033] v: scanning speed of the laser beam (mm / s).

[0034] [9] A method for manufacturing a ceramic-metal joint according to any one of [1] to [6] above, wherein the solid metal material contains Ag as a main component, and the ceramic substrate contains AlN or Si3N4 as a main component.

[0035]

[10] The method for producing a ceramic-metal joint according to [9] above, wherein one or more laser beams are used so that the average irradiation energy density E expressed by the following formula (1) is 25 to 160 J / mm 2 The laser beam is irradiated onto the surface of the ceramic substrate.

[0036] E=(P L1 / D L1 +P L2 / D L2 +···+P Ln / D Ln ) / v…(1)

[0037] in,

[0038] E: Average irradiation energy density E (J / mm 2 )

[0039] Symbol Li (i=integer greater than or equal to 1 and less than or equal to n, where n is the total number of laser beams used): identification symbol of each laser beam used

[0040] P Li : Laser output power of laser beam Li (W)

[0041] D Li : The irradiation spot diameter at right angles to the scanning direction of the laser beam Li (mm)

[0042] v: scanning speed of the laser beam (mm / s).

[0043] In this specification, the so-called "irradiation point (spot)" means the area on the surface of the ceramic substrate irradiated by the forward path of a certain laser beam. At least one of the laser beams used needs to hit the metal material being fed. For the laser beam that hits the metal material being fed, the area on the surface of the ceramic substrate that is irradiated when it is assumed to reach the surface of the ceramic substrate without being blocked by the metal material being fed in the middle of its forward path is set as the "irradiation point" of the laser beam. The so-called "irradiation area (area)" means the area composed of the positions on the surface of the ceramic substrate belonging to any irradiation point. When only one laser beam is used, the "irradiation area" and the "irradiation point" must be consistent. When multiple laser beams are used, the range of each "irradiation point" is consistent with or smaller than the range of the "irradiation area", and when all the irradiation points generated by each laser beam are consistent, the "irradiation area" is consistent with each "irradiation point".

[0044] "Main component" means a component whose content expressed as a mass ratio is 50% or more among the components constituting the substance. For example, "solid metal material with Cu as the main component" means a solid metal material with a Cu content of 50% or more by mass. "Ceramic substrate with AlN as the main component" means a ceramic substrate with an AlN content of 50% or more by mass. It should be noted that in this specification, metal materials with Cu as the main component are referred to as "copper-based", and metal materials with Ag as the main component are referred to as "silver-based".

[0045] Effects of the Invention

[0046] According to the present invention, a "ceramic-metal joint" in which a metal layer is directly formed on the surface of a ceramic substrate can be obtained by using a laser metal deposition method. The above-mentioned metal layer can be made into a thin wire shape with a width of 0.5 mm or less, so the present invention can be used as a method for directly forming a copper-based metal circuit pattern on an insulating substrate for mounting semiconductor elements. In addition, it can be used as a manufacturing method for a "solder-integrated ceramic plate" that selectively bonds a silver-based solder to a specified position. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a diagram schematically illustrating the configuration of a laser metal deposition device that can be used in the present invention.

[0048] Figure 2 This is an example of the height profile of the linear metal layer obtained in Example 1 measured in the width direction using a laser microscope.

[0049] Figure 3 This is an example of the height profile of the linear metal layer obtained in Example 2 measured in the width direction using a laser microscope.

[0050] Figure 4This is an example of the height profile of the linear metal layer obtained in Example 3 measured in the width direction using a laser microscope.

[0051] Figure 5 This is an example of the height profile of the linear metal layer obtained in Example 4 measured in the width direction using a laser microscope.

[0052] Figure 6 This is an example of the height profile of the linear metal layer obtained in Example 5 measured in the width direction using a laser microscope.

[0053] Figure 7 The following are photographs showing the appearance of the ceramic plate after the metal layer preparation test was performed in each example. DETAILED DESCRIPTION

[0054] exist Figure 1 The structure of the laser metal deposition device that can be used in the present invention is schematically illustrated in the figure. As an example, a representative structure of the two-beam irradiation type is shown, but a device of a type that irradiates only one beam or a type that irradiates three or more beams can also be used. The processing head 10 is a unit having means for spraying metal powder as a coating material in a prescribed direction and means for irradiating a laser beam in a prescribed direction, and is capable of moving in a horizontal direction above the ceramic substrate 1 while maintaining a prescribed distance from the surface of the ceramic substrate 1. The metal powder as the coating material is introduced into the processing head 10 from the powder supply device 20 using the powder supply pipe 21, and is sprayed onto the surface of the ceramic substrate 1 from the powder feeding nozzle 22 installed on the processing head 10. The flying metal powder sprayed from the powder feeding nozzle 22 is indicated by the reference numeral 200 in the figure. On the other hand, the lasers generated by the laser generating devices 30a and 30b are introduced into the processing head 10 using optical fibers 31a and 31b, respectively, and the laser beams 300a and 300b are irradiated in a predetermined direction from a lens (not shown) built into the processing head 10. Figure 1 In the example of FIG. 1 , the metal powder is ejected and the laser beam is irradiated while the processing head 10 is moved in the direction of the arrow.

[0055] Laser beams 300a and 300b are irradiated on the flying metal powder 200, and while the solid metal powder 200 is heated, the surface of the ceramic substrate 1 is also irradiated, and the area on the surface of the ceramic substrate 1 irradiated with these laser beams, that is, the irradiation area 310 is heated. Almost all particles of the metal powder 200 melt in flight, and when reaching the irradiation area 310, the molten particles can be included. That is, the solid metal material as the coating material is melted during the feeding when irradiated by the laser beam or when it reaches the surface of the ceramic substrate. In addition, the particle size of the metal powder 200 in the figure is exaggerated for description.

[0056] By sufficiently heating the irradiation area 310, the obtained molten metal is coated on the surface of the ceramic substrate 1 while being kept in a molten state. That is, it is important that the molten metal does not solidify and bounce off immediately when it reaches the ceramic substrate 1, and it stays in a molten state (even if it stays for a short time) on the surface of the ceramic substrate 1. In this short time, the surface of the ceramic substrate 1 is maintained wetted by the molten metal. The molten metal coated on the ceramic substrate 1 solidifies after leaving the scanned irradiation area 310 as the processing head 10 moves, and a metal layer 2 is formed in a linear shape in the area on the surface of the ceramic substrate 1 through which the irradiation area 310 passes. The metal layer 2 is firmly bonded to the ceramic substrate 1 during the solidification process. In this way, a "ceramic-metal joint" is constructed in which the metal layer 2 is bonded to the surface of the ceramic substrate 1. If the irradiation area 310 is scanned on the ceramic substrate 1 in a direction perpendicular to the scanning, a planar metal layer 2 can also be formed.

[0057] The space between the processing head 10 and the ceramic substrate 1 where the molten metal is generated and the surface of the ceramic substrate 1 including the irradiation area 310 are preferably shielded with an inert gas such as Ar to prevent oxidation of the metal. Figure 1 The record is omitted, for example, the following mechanism can be adopted: a sleeve surrounding each laser beam and the powder feeding nozzle 22 is provided at the lower part of the processing head 10 so that its lower end does not contact the ceramic substrate 1, a shielding gas is supplied from the processing head 10 into the above-mentioned sleeve, and the shielding gas ejected from the lower end of the above-mentioned sleeve is sprayed onto the surface area of ​​the ceramic substrate 1 including the irradiation area 310.

[0058] exist Figure 1 , an example of forming an irradiation area 310 using a common irradiation point generated by two laser beams 300a and 300b is shown. As another irradiation method, for example, the following method can be used: among multiple laser beams, a part of the laser beams is directed to a position where the flying powder is easy to melt, and the focus is adjusted, and the focus of the other laser beams is adjusted in a manner to most effectively heat the surface of the ceramic substrate 1. In addition, Figure 1 In the example, as a method of feeding the coating material, ie, solid metal, a method of ejecting metal powder from the powder feeding nozzle 22 is shown, but a method of feeding, for example, a wire rod instead of powder may also be adopted.

[0059] [Solid metal material]

[0060] As the solid metal material used as the raw material of the coating material, materials with elements such as Cu, Ag, Ti, Ni, Al, Fe, Au, Pt as the main component can be used. A method for directly joining metals with these elements as the main component in the form of fine wires on a ceramic substrate has not yet been established. In particular, copper-based metals are widely used as circuit metals for insulating circuit substrates, and silver-based metals are widely used as solders. Therefore, when used in such applications, materials with Cu or Ag as the main component can be used.

[0061] More specifically, as the copper-based metal for circuits, pure copper having a Cu content of 99.9 mass % or more is preferably used.

[0062] As the silver-based metal used as the solder, a metal having a composition near the eutectic of the Ag-Cu system is preferred. As the active metal, it is more preferred to contain 0.5 to 5% by mass of Ti. For example, a solder of an Ag-Cu-Ti alloy with 23 to 33% by mass of Cu, 0.5 to 5% by mass of Ti, and the remainder being Ag can be cited. In addition, various Ag solders specified in JIS Z3261:1998 can be applied.

[0063] When metal powder is used as the solid metal material, a powder having a cumulative 50% particle size D50 of, for example, 5 to 100 μm in a volume-based particle size distribution using a laser diffraction / scattering method, and more preferably 10 to 30 μm can be used. A mixed powder of two or more metal powders in a predetermined ratio can be used.

[0064] [Ceramic substrate]

[0065] As a ceramic substrate, various materials of ceramic substrates are applied. For example, substrates with aluminum nitride (AlN) as the main component, substrates with silicon nitride (Si3N4) as the main component, substrates with aluminum oxide (Al2O3) as the main component, etc. can be listed. In the case of constructing an insulating circuit substrate, a ceramic plate with a thickness of, for example, about 0.25 to 1.0 mm can be used.

[0066] [laser]

[0067] In the present invention, the energy of the laser beam is used to melt the solid metal materials of various metals represented by copper and silver. When a metal material containing Cu is used, it is effective to use a laser with a wavelength of 600nm or less. When a plurality of laser beams are used, it is preferred that at least one of them is a laser with a wavelength of 600nm or less. As a representative laser with a wavelength of 600nm or less, a cyan laser with a wavelength of about 450nm can be cited.

[0068] [Average irradiation energy density E]

[0069] In the present invention, in order to join ceramics with metals, it is important to coat the ceramic surface with molten metal, that is, to make the ceramic surface wetted by molten metal. Ceramics are substances mainly composed of high-melting-point inorganic compounds, which are heterogeneous substances with metals. Even for a short time, if the surface of the ceramic substrate is not wetted by molten metal, it is difficult to achieve the joining of the ceramic substrate and the solidified metal. If it is a spraying method, since the amount of molten metal sprayed on the surface of the ceramic substrate is large, and the heat given to the ceramic substrate by plasma is also large, it is easy to ensure the wetting of the ceramic and the molten metal. When a small amount of metal is melted to form a thin wire-shaped metal layer with a width of, for example, less than 0.5 mm using the energy of the laser, there is a problem that the molten metal is easy to solidify immediately when it reaches the surface of the ceramic substrate. Therefore, the results of the study show that by intentionally irradiating the surface of the ceramic substrate with a laser beam and sufficiently heating the irradiated area, the molten metal can be coated on the ceramic surface, and it is confirmed that the joining of the ceramic substrate and the thin wire-shaped metal layer can be achieved.

[0070] The energy of the laser beam applied to the irradiation area on the surface of the ceramic substrate is sufficient as long as it is an intensity that can achieve coating with the molten metal. More specifically, when the coating material metal is mainly composed of Cu and the ceramic substrate is mainly composed of AlN, one or more laser beams are used so that the average irradiation energy density E expressed by the following formula (1) becomes 80 to 160 J / mm 2 In addition, when the coating material metal has Ag as the main component and the ceramic substrate has AlN or Si3N4 as the main component, one or more laser beams are used with an average irradiation energy density E expressed by the following formula (1) becoming 25 to 160 J / mm 2 The mode setting is valid.

[0071] E=(P L1 / D L1 +P L2 / D L2 +···+P Ln / D Ln ) / v…(1)

[0072] in,

[0073] E: Average irradiation energy density E (J / mm 2 )

[0074] Symbol Li (i=integer greater than or equal to 1 and less than or equal to n, where n is the total number of laser beams used): identification symbol of each laser beam used

[0075] P Li : Laser output power of laser beam Li (W)

[0076] D Li : The irradiation spot diameter at right angles to the scanning direction of the laser beam Li (mm)

[0077] v: Scanning speed of laser beam (mm / s)

[0078] When the right side of the above equation (1) is expanded, it is expressed as the following equation (2).

[0079] E=P L1 / (D L1 ×v)+P L2 / (D L2 ×v)+···+P Ln / (D Ln ×v)……… (2)

[0081] Here, taking the case of using only one laser beam as an example, the above equation (2) can be expressed as the following equation (2-1).

[0082] E=P L1 / (D L1 ×v)…(2-1)

[0083] P of molecule L1 is the laser output power (W), which is equivalent to the energy per 1 second (unit: [J / s]). L1 ×v represents the beam scanning area per second (unit: [mm] · [mm / s] = [mm 2 / s]). When the trajectory through which the center of the irradiation point on the surface of the ceramic substrate passes is called the "scan axis", in the area through which the irradiation point passes in 1 second, the closer to the position of the scan axis, the longer the time the irradiation point passes, and thus the higher the energy imparted. Therefore, E (unit: [J / s] / [mm 2 / s]=[J / mm 2 ]) can be considered as an indicator of the average energy per unit area for 1 second of irradiation. Therefore, in the present invention, the above E is referred to as the "average irradiation energy density E". The laser beam also hits the metal of the coating material being fed on the way to the irradiation point on the surface of the ceramic substrate, so the laser output power P L1 The above average irradiation energy density E can be regarded as the laser output power P which is divided into the part irradiating the cladding material metal and the part directly irradiating the surface of the ceramic substrate. L1 This was converted into a value of average energy per unit area of ​​the region through which the irradiation point on the surface of the ceramic substrate passed during 1 second of irradiation.

[0084] The average irradiation energy density E when using a plurality of laser beams can be regarded as the sum of the average irradiation energy densities E given to the irradiation area by the irradiation points of the respective laser beams, as represented by the above-mentioned formula (2).

[0085] In order to achieve the coating of the molten metal on the surface of the ceramic substrate, it is advantageous to increase the average irradiation energy density E. According to the inventors' research, when the coating material metal has Cu as the main component and the ceramic substrate has AlN as the main component, it is preferred to use one or more laser beams so that the average irradiation energy density E of the above formula (1) is 80 J / mm 2 More preferably 90 J / mm 2 In addition, as long as the coating material metal has Ag as the main component (for example, Ag-Cu brazing filler metal such as Ag-Cu-Ti alloy), when the ceramic substrate has AlN or Si3N4 as the main component, it is preferred to use one or more laser beams so that the average irradiation energy density E of the above formula (1) becomes 25 J / mm 2 More than 40 J / mm 2 In particular, when the ceramic substrate has AlN as the main component, 50 J / mm 2 More preferably, 60 J / mm 2 On the other hand, if the average irradiation energy density E becomes larger, the ceramic substrate is more likely to be damaged. Even if the main component of the ceramic substrate is either AlN or Si3N4, the average irradiation energy density E is preferably 160 J / mm 2 The following range is set, more preferably 120 J / mm 2 The following range is set. In addition, the feed amount of the metal material per unit time needs to be adjusted according to the irradiation conditions of the laser beam so that the fed metal material is sufficiently melted.

[0086] Example

[0087] Use with Figure 1 The two-beam irradiation type laser metal deposition apparatus having the structure shown above was used to attempt to bond a thin line-shaped metal layer made of a copper-based metal or a silver-based metal to the surface of a ceramic substrate. The experimental method is described below.

[0088] As ceramic substrates, aluminum nitride (AlN) plates (manufactured by TD Pallet Iron & Steel Co., Ltd.) with a size of 30 mm square and a thickness of 1 mm and silicon nitride (Si3N4) plates (manufactured by MARUWA Co., Ltd.) with a size of 30 mm square and a thickness of 1 mm were prepared. As metal materials for coating materials, copper powder (manufactured by Sanyo Special Steel Co., Ltd.) with a cumulative 50% particle size D50 of 29.0 μm and a purity of 99.96% and Ag-Cu-Ti alloy powder (manufactured by Kojundo Chemical Research Institute Co., Ltd.) with a cumulative 50% particle size D50 of 24.3 μm and a composition of Ag: 70.92 mass%, Cu: 27.58 mass%, and Ti: 1.50 mass% were prepared.

[0089] The aluminum nitride plate or silicon nitride plate (hereinafter sometimes referred to as "ceramic plate") is fixed on a horizontal plate so that one side of the surface faces vertically upward, while the processing head ( Figure 1 10) in the horizontal direction ( Figure 1 The copper powder or Ag-Cu-Ti alloy powder (hereinafter sometimes referred to as "metal powder") is melted as follows. A laser generator (two systems of laser metal deposition device) is used. Figure 1 30a, 30b), each generating cyan laser light, from the processing head to the ceramic plate ( Figure 1 The surface of the reference numeral 1) is irradiated with two laser beams, and at the same time, the powder feeding nozzle ( Figure 1 22) is ejected by Ar gas contained in the powder supply device ( Figure 1 The distance between the ejection port (lower end) of the powder feeding nozzle and the surface of the ceramic plate is about 5 mm. The two laser beams are irradiated in a manner that the irradiation points formed on the surface of the ceramic plate are consistent. That is, the irradiation area ( Figure 1 The reference numeral 310 in the figure is the same size as each irradiation point. In addition, the irradiation point of each laser beam is circular. The metal powder as the coating material is ejected and fed in the direction toward the above-mentioned irradiation area, so that the beam of at least one of the above-mentioned two laser beams hits the metal powder being fed, and almost all of the metal powder being fed is melted before reaching the irradiation area (including when reaching the irradiation area). At the lower part of the processing head, a sleeve surrounding each laser beam and the powder feeding nozzle is provided so that the lower end thereof is about 5 mm from the surface of the ceramic plate. During the laser beam irradiation, Ar gas is frequently supplied from the processing head into the above-mentioned sleeve as a shielding gas, and the Ar gas ejected from the lower end of the above-mentioned sleeve is sprayed on the surface area of ​​the ceramic plate including the irradiation area.

[0090] In this way, the metal powder was melted while scanning the irradiation area of ​​about 20 mm, and a linear metal layer was attempted to be joined on the surface of the ceramic plate. The test conditions and results of each example are summarized in Table 1 and Table 2. In Table 1 and Table 2, the two laser beams are distinguished as beams 1 and 2, respectively. The above (1) is expressed as the following formula (1-2) here.

[0091] E=(P L1 / D L1 +P L2 / D L2 ) / v…(1-2)

[0092] E: Average irradiation energy density (J / mm 2 )

[0093] P L1 , P L2 : Laser output power of beam 1 and 2 respectively (W)

[0094] D L1 , D L2 : The irradiation spot diameters of beams 1 and 2 respectively (mm)

[0095] v: Scanning speed of laser beam (mm / s)

[0096] The formation of the metal layer was evaluated using the following criteria, and an evaluation of ○ was determined to be acceptable.

[0097] ○: The linear metal layer is bonded to the surface of the ceramic plate.

[0098] Δ: Linear metal solidification was formed on the surface of the ceramic plate, but the metal solidification was not bonded to the ceramic plate.

[0099] ×: On the surface of the ceramic plate, the molten metal scatters and no linear metal solidification is formed.

[0100] [Comparative Example 1]

[0101] As a ceramic plate, the aluminum nitride plate was used. Beams 1 and 2 both used a cyan laser with a wavelength of 450nm, and the laser output power was set to 40W, and the irradiation point diameter was set to 0.26mm. The copper powder was fed at a supply rate of 10mg / s, and the scanning speed of the irradiation point was set to 5.0mm / s. The flow rate of the shielding gas was 10L / min. The average irradiation energy density E calculated using the above formula (1-2) was 61.5J / mm 2 .

[0102] Under this condition, the molten metal did not cover the ceramic plate, and no linear metal solidification was formed (× evaluation).

[0103] [Comparative Example 2]

[0104] The formation of the metal layer was attempted under the same conditions as in Comparative Example 1 except that the laser output powers of beams 1 and 2 were both 45 W. The average irradiation energy density E was 69.2 J / mm 2 .

[0105] Under this condition, the molten metal did not cover the ceramic plate, and no linear metal solidification was formed (× evaluation).

[0106] [Comparative Example 3]

[0107] The formation of the metal layer was attempted under the same conditions as in Comparative Example 1 except that the laser output powers of beams 1 and 2 were both 50 W. The average irradiation energy density E was 76.9 J / mm 2 .

[0108] It is considered that under this condition, the molten metal failed to sufficiently cover the ceramic plate, and although linear metal solidification was formed, it did not achieve bonding with the ceramic plate (△ evaluation).

[0109] [Example 1]

[0110] The formation of the metal layer was attempted under the same conditions as in Comparative Example 1 except that the laser output power of beams 1 and 2 was 55 W. The average irradiation energy density E was 84.6 J / mm 2 .

[0111] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0112] exist Figure 2 An example of the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, is shown in FIG. The line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam (= the irradiation point diameter of beams 1 and 2), and the thickness (top height) of the metal layer is about 160 μm. It was confirmed that the thin wire-shaped metal layer can be bonded to the surface of the ceramic substrate (the same applies to the following examples).

[0113] [Example 2]

[0114] The formation of the metal layer was attempted under the same conditions as in Comparative Example 1 except that the laser output powers of beams 1 and 2 were both 60 W. The average irradiation energy density E was 92.3 J / mm 2 .

[0115] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0116] exist Figure 3An example of the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, is shown in FIG. The line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness (top height) of the metal layer is about 180 μm.

[0117] The shear strength (joining strength) of the ceramic-metal joint body to which the linear metal layer was joined under the same conditions as in this example was examined by the following method.

[0118] (Method for measuring shear strength)

[0119] The ceramic-metal joint body was cut into 10 mm width perpendicular to the length direction of the linear metal layer of the ceramic-metal joint body to prepare an evaluation sample. The evaluation sample was installed in a shear tester (model: SPST2000N) manufactured by Adwells Co., Ltd., and the shear strength was measured by applying an external force in a direction perpendicular to the length direction of the linear metal layer and parallel to the ceramic surface to the linear metal layer using a shear tool at a conveying speed of 0.25 mm / sec.

[0120] As a result, the shear strength was 26.6 MPa.

[0121] [Example 3]

[0122] The formation of the metal layer was attempted under the same conditions as in Comparative Example 1 except that the laser output powers of beams 1 and 2 were both 65 W. The average irradiation energy density E was 100.0 J / mm 2 .

[0123] Even under this condition, the molten metal was able to fully cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (○ evaluation). The shear strength of the ceramic-metal bonded body bonded with the linear metal layer under the same conditions as in this example was studied using the above method, and the result was 38.1 MPa.

[0124] exist Figure 4 An example of the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, is shown in FIG. The line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness (top height) of the metal layer is about 206 μm.

[0125] [Example 4]

[0126] The formation of the metal layer was attempted under the same conditions as in Comparative Example 1 except that the laser output powers of beams 1 and 2 were both 70 W. The average irradiation energy density E was 107.7 J / mm 2 .

[0127] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0128] exist Figure 5 An example of the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, is shown in FIG. The line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness (top height) of the metal layer is about 215 μm.

[0129] [Example 5]

[0130] The formation of the metal layer was attempted under the same conditions as in Comparative Example 1 except that the laser output powers of beams 1 and 2 were both 75 W. The average irradiation energy density E was 115.4 J / mm 2 .

[0131] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0132] exist Figure 6 An example of the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, is shown in FIG. The line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness (top height) of the metal layer is about 206 μm.

[0133] [Example 6]

[0134] As the ceramic plate, the silicon nitride plate mentioned above was used. Beams 1 and 2 both used a cyan laser with a wavelength of 450nm, and the laser output power was set to 20W, and the irradiation point diameter was set to 0.26mm. The above-mentioned Ag-Cu-Ti alloy powder was fed at a supply rate of 10mg / s, and the scanning speed of the irradiation point was set to 5.0mm / s. The flow rate of the shielding gas was 10L / min. The average irradiation energy density E calculated using the above (1-2) formula was 30.8J / mm 2 .

[0135] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0136] According to the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, it can be seen that the line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness of the metal layer (top height) is about 94μm.

[0137] [Example 7]

[0138] The formation of the metal layer was attempted under the same conditions as in Example 6 except that the laser output powers of beams 1 and 2 were both 25 W. The average irradiation energy density E was 38.5 J / mm 2 .

[0139] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0140] According to the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, it can be seen that the line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness of the metal layer (top height) is about 117μm.

[0141] [Example 8]

[0142] The formation of the metal layer was attempted under the same conditions as in Example 6 except that the Ag-Cu-Ti alloy powder was fed at a feed rate of 5 mg / s. The average irradiation energy density E was 30.8 J / mm 2 .

[0143] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0144] According to the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, it can be seen that the line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness of the metal layer (top height) is about 83μm.

[0145] [Example 9]

[0146] The formation of the metal layer was attempted under the same conditions as in Example 6 except that the Ag-Cu-Ti alloy powder was fed at a feed rate of 12.5 mg / s. The average irradiation energy density E was 30.8 J / mm 2 .

[0147] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0148] According to the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, it can be seen that the line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness of the metal layer (top height) is about 110μm.

[0149] [Example 10]

[0150] The formation of the metal layer was attempted under the same conditions as in Example 6 except that the Ag-Cu-Ti alloy powder was fed at a feed rate of 15 mg / s. The average irradiation energy density E was 30.8 J / mm 2 .

[0151] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0152] According to the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, it can be seen that the line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness of the metal layer (top height) is about 107μm.

[0153] [Example 11]

[0154] The formation of the metal layer was attempted under the same conditions as in Example 6 except that the laser output power of beams 1 and 2 was 40 W and the Ag-Cu-Ti alloy powder was fed at a feeding rate of 15 mg / s. The average irradiation energy density E was 61.5 J / mm 2 .

[0155] Even under this condition, the molten metal can fully cover the ceramic plate, and the linear metal layer is bonded to the ceramic plate (○ evaluation). The shear strength of the ceramic-metal bonded body bonded with the linear metal layer under the same conditions as in this example was studied in the same manner as in Example 2, and the result was a shear strength of 92.0 MPa or more.

[0156] According to the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, it can be seen that the line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness of the metal layer (top height) is about 167μm.

[0157] [Example 12]

[0158] The formation of the metal layer was attempted under the same conditions as in Example 6 except that the laser output power of beams 1 and 2 was 35 W and the Ag-Cu-Ti alloy powder was fed at a feeding rate of 12.5 mg / s. The average irradiation energy density E was 53.8 J / mm 2 .

[0159] Even under this condition, the molten metal can fully cover the ceramic plate, and the linear metal layer is bonded to the ceramic plate (○ evaluation). The shear strength of the ceramic-metal bonded body bonded with the linear metal layer under the same conditions as in this example was studied in the same manner as in Example 2, and the result was a shear strength of 42.2 MPa or more.

[0160] According to the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, it can be seen that the line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness of the metal layer (top height) is about 165μm.

[0161] [Example 13]

[0162] As the ceramic plate, the aluminum nitride plate was used. Beams 1 and 2 both used a cyan laser with a wavelength of 450nm, and the laser output power was set to 45W, and the irradiation point diameter was set to 0.26mm. The above-mentioned Ag-Cu-Ti alloy powder was fed at a supply rate of 5mg / s, and the scanning speed of the irradiation point was set to 5.0mm / s. The flow rate of the shielding gas was 10L / min. The average irradiation energy density E calculated using the above (1-2) formula was 69.2J / mm 2 .

[0163] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0164] According to the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, it can be seen that the line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness of the metal layer (top height) is about 74μm.

[0165] [Example 14]

[0166] The formation of the metal layer was attempted under the same conditions as in Example 13 except that the laser output powers of beams 1 and 2 were both 55 W. The average irradiation energy density E was 84.6 J / mm 2 .

[0167] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0168] According to the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, it can be seen that the line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness of the metal layer (top height) is about 60μm.

[0169] [Example 15]

[0170] The formation of the metal layer was attempted under the same conditions as in Example 13 except that the laser output power of beams 1 and 2 was 50 W and the Ag-Cu-Ti alloy powder was fed at a feeding rate of 10 mg / s. The average irradiation energy density E was 76.9 J / mm 2 .

[0171] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0172] According to the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, it can be seen that the line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness of the metal layer (top height) is about 64μm.

[0173] [Example 16]

[0174] The formation of the metal layer was attempted under the same conditions as in Example 13 except that the laser output power of beams 1 and 2 was both 55 W and the Ag-Cu-Ti alloy powder was fed at a feed rate of 7.5 mg / s. The average irradiation energy density E was 84.6 J / mm 2 .

[0175] Even under these conditions, the molten metal could sufficiently cover the ceramic plate, and the linear metal layer was bonded to the ceramic plate (evaluation of "○").

[0176] According to the height profile of the linear metal layer bonded to the ceramic plate obtained in this example, measured in the width direction of the linear metal layer using a laser microscope, it can be seen that the line width roughly corresponds to the diameter of the irradiation area of ​​the laser beam, and the thickness of the metal layer (top height) is about 73μm.

[0177]

[0178]

[0179] exist Figure 7 The figure shows the appearance of the ceramic plate after the metal layer production test of each example. The ceramic plate on the left shows the results of Comparative Examples 1, 2, 3, and Example 1, and the ceramic plate on the right shows the results of Examples 2, 3, 4, and 5. The value (wattage) recorded on the plate is the total laser output power (W) of beams 1 and 2.

[0180] Description of Reference Numerals

[0181] 1 Ceramic substrate

[0182] 2 Metal Layer

[0183] 10 Processing head

[0184] 20 Powder supply device

[0185] 21 Powder supply pipe

[0186] 22 Powder feeding nozzle

[0187] 30a, 30b Laser generating device

[0188] 31a, 31b optical fiber

[0189] 200 Metal powder

[0190] 300a, 300b Laser beam

[0191] 310 Irradiation Area

Claims

1. A method for producing a ceramic-metal joint, wherein: The surface of the ceramic substrate is irradiated while being scanned with a laser beam, and solid metal material is fed to an area on the surface of the ceramic substrate irradiated with the laser beam (hereinafter referred to as the "irradiation area"), so that the metal material being fed is also irradiated by the laser beam, and the surface of the ceramic substrate located in the irradiation area is heated and melted, and the molten metal material covers the surface of the ceramic substrate and then solidifies.

2. The method for producing a ceramic-metal joint according to claim 1, wherein: The solid metal material is powder.

3. The method for producing a ceramic-metal joint according to claim 1, wherein: The solid metal material contains any one of Cu, Ag, Ti, Ni, Al, Fe, Au, and Pt as a main component.

4. The method for producing a ceramic-metal joint according to claim 1, wherein: The solid metal material contains Cu or Ag as a main component.

5. The method for producing a ceramic-metal joint according to claim 1, wherein: One or more laser beams are used, and at least one of the laser beams irradiating the metal material being fed has a wavelength of 600 nm or less.

6. The method for producing a ceramic-metal joint according to claim 1, wherein: Using one or more laser beams, at least one of the laser beams irradiating the metal material being fed uses any one of Yb-doped solid laser, Nd-doped solid laser, GaN semiconductor laser, copper vapor laser, Ar gas laser, N2 gas laser, and excimer laser as a light source.

7. The method for producing a ceramic-metal joint according to claim 1, wherein: The solid metal material contains Cu as a main component, and the ceramic substrate contains AlN as a main component.

8. The method for producing a ceramic-metal joint according to claim 7, wherein: One or more laser beams are used so that the average irradiation energy density E expressed by the following formula (1) is 80 to 160 J / mm 2 The laser beam is irradiated onto the surface of the ceramic substrate. E=(P L1 / D L1 +P L2 / D L2 +···+P Ln / D Ln ) / v…(1) in, E: Average irradiation energy density E (J / mm 2 ) Symbol Li (i=integer greater than or equal to 1 and less than or equal to n, where n is the total number of laser beams used): identification symbol of each laser beam used P Li : Laser output power of laser beam Li (W) D Li : The irradiation spot diameter at right angles to the scanning direction of the laser beam Li (mm) v: scanning speed of the laser beam (mm / s).

9. The method for producing a ceramic-metal joint according to claim 1, wherein: The solid metal material has Ag as a main component, and the ceramic substrate has AlN or Si3N4 as a main component.

10. The method for producing a ceramic-metal joint body according to claim 9, wherein: One or more laser beams are used so that the average irradiation energy density E expressed by the following formula (1) is 25 to 160 J / mm 2 The laser beam is irradiated onto the surface of the ceramic substrate. E=(P L1 / D L1 +P L2 / D L2 +···+P Ln / D Ln ) / v…(1) in, E: Average irradiation energy density E (J / mm 2 ) Symbol Li (i=integer greater than or equal to 1 and less than or equal to n, where n is the total number of laser beams used): identification symbol of each laser beam used P Li : Laser output power of laser beam Li (W) D Li : The irradiation spot diameter at right angles to the scanning direction of the laser beam Li (mm) v: scanning speed of the laser beam (mm / s).

Citation Information

Patent Citations

  • How to create a strong bond between a copper layer and a ceramic

    JP1995501855A

  • Metallized substrate

    JP2006089290A

  • Coating method

    JP2022013563A

  • Laser machining device and laser machining method

    WO2017170890A1